Impact of Usability to User Experience on blanja.com Site - Hanny Zora Agustina (AIBPM Publisher, 2020)
E-commerce business continues to grow in the world, one of which is Blanja.com, a joint venture with the world's largest marketplace Ebay. However, problems arose in sales due to the 56.39% increase in the bounce rate resulting in a low conversion rate. The purpose of this research is to find out how the usability aspects such as learnability, efficient, error, memorability, and satisfaction affect user experience at Blanja.com. Data analysis was performed using statistical modelling techniques of Structural Equation Modelling, (confirmatory) with CFA and path analysis with LISREL statistics. Several results were obtained that the user did not easily understand the content aspect. It was difficult to get information, the hyperlinks were unclear, problems with navigation occurred. Although the users enjoyed it because of the responsive customer service, they were still not satisfied because of the background display, colours and graphics. Through this research, some general guidelines in ecommerce design can be generated to provide a better experience to users.